Peran Pustakawan di Era Digital: Penguatan Literasi Informasi melalui Kuliah Umum dan Lomba Kreatif di Universitas Sam Ratulangi - Ridwan, Madinatul Munawwarah; Runtuwene, Anita; Nalole, Suci Ramadhani; Rawung, Lidya Ivana; Waleleng, Grace Jane; Idrus, Muhammad Ikram (LESTARI: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community engagement program aimed to strengthen information literacy competencies and enhance understanding of the role of digital-age librarians among students of the Library and Information Science Program at Sam Ratulangi University. The activity was conducted on 14 September 2024 and involved 81 participants, including students, lecturers, and alumni working in the library profession. The implementation consisted of a public lecture titled “The Role of Librarian in the Digital Era”, followed by two creative competitions: a Book Cataloging Competition and an Information Literacy Storytelling Competition. Evaluation instruments included a pre-test and post-test questionnaire with ten five-point Likert items, as well as scoring rubrics (1–5 scale) for both competitions. Data were analyzed descriptively using mean scores, percentages, and score differences. The results show a substantial improvement in participants’ information literacy understanding, with average scores increasing from 58 (pre-test) to 84 (post-test), representing a 44.8% gain. The proportion of participants able to identify key roles of digital librarians rose from 36% to 79%. In the Book Cataloging Competition, 70% of participants achieved “good” to “excellent” scores, while 67% scored highly in clarity and creativity in the storytelling competition. These indicators demonstrate the effectiveness of the program in enhancing cataloging skills, information communication abilities, and digital librarianship awareness. Academically, this program offers a replicable model for integrating public lectures and creative assessment into information literacy education and community outreach in library and information science.